Numerical analysis of seal force in contacting finger seal - Wei, Yuan; Ma, Bowen; Li, Yi; Schröder, Kai-Uwe (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
A finger seal is a flexible sealing device widely used in high-temperature and high-pressure environments such as gas turbines. Its force analysis is the key to the design and optimization of finger seal performance. At present, most of the research on force analysis of finger seals is focused on the whole seal ring, but each finger beam has a different contact performance with the shaft. In this paper, a new force analysis method for contacting finger seals is proposed, as well as the model of finger seals with or without eccentricity is established to analyze the force of a single finger beam. The curved flexible finger beam is transformed into a straight one loaded with a certain moment at the end of it. The force acting on the finger beam is studied and compared with the existing reference to demonstrate the feasibility of the analysis method. By changing each parameter of the finger seal, the relationship between seal force and structural parameter is investigated. It shows that this method is meaningful to the calculation results of seal force for single finger beam and can promote the development of finger seal and make it further in engineering application.